Pengaruh Penambahan Massa Magnesium Oksida (MgO), Suhu Dan Waktu Tahan Terhadap Karakteristik Keramik Komposit Dari Abu Dasar Batubara, Limbah Kaleng Aluminium Dan Air Bittern - Abdul Aziz; Roniyus Marjunus; Posman Manurung (Journal of Energy, Material, and Instrumentation Technology, 2026)
The synthesis of silica and alumina from coal bottom ash and aluminum can waste was carried out to produce raw materials for composite ceramics. This study aimed to analyze the chemical characteristics of silica (SiO2) and alumina (Al2O3) extracted from coal bottom ash and aluminum can waste, evaluate the physical properties of the resulting composite ceramics, and compare their quality with commercially produced ceramic materials. Silica was extracted from coal bottom ash using the sol-gel method, while composite ceramics were prepared using the solid-state method. The ceramic samples were fabricated with MgO additions of 0, 10, and 15 wt%, sintering temperatures ranging from 800 to 1100 degC, and holding times of 2, 3, and 4 h. Physical characterization included density, porosity, water absorption, and compressive strength measurements. Chemical composition was analyzed using X-ray fluorescence (XRF), while compressive strength was determined using a Universal Testing Machine (UTM). The characterization results showed that the extracted silica and alumina contained 43.51% SiO2 and 31.01% Al2O3, respectively. The optimum ceramic sample exhibited a density of 1.42 g/cm3, porosity of 45.66%, water absorption of 32.11%, and compressive strength of 2.37 MPa. Although the synthesized composite ceramics demonstrated promising properties, their overall quality remained lower than that of commercially manufactured ceramic materials.